Developing Pop Up Book Learning Media On Theme 8 For First Grade In MI Islamiyah Pancakarya - Zaqiyatul Muna; Ma’as Shobirin; Ummu Jauharin Farda (ZAHRA: Research and Tought Elementary School of Islam Journal, 2022)
There are students who seem bored and drenched by the monotonous learning since they simply have to listen to the teacher's instruction, and there are even other students who are rushing about the classroom because the learning media employed by the teacher are not being utilized effectively. This research aims to develop the need for a pop-up media book for both teachers and students, as well as the validation of a pop-up media book on topic 8 for the first grade of Islamic elementary school MI Islamiyah Pancakarya Semarang. This approach to data collection research and development (R&D) research methodologies across the five stages of potential and problem, data collection, product design, design validation, and design revision. The data gathering methods include anglets, observations, interviews, and documentation, while the data processing methods include qualitative and quantitative analysis. This investigation resulted in a suitable media category for topic 8 of the first-grade MI Islamiyah Pancakarya Semarang thematic study. The overall harmonic character of the content is validated by the evaluation of 4.57 in the "very excellent" category, or 91.42 percent (very valid). Validation of the language aspect receives a score of 4.50, which falls into the "excellent" category, or 90.00% (very valid). The validation of media specialists on all areas of accessibility and visual view received a score of 4.40 in the "very good" category, or 88.0% (very valid). This research is limited to the product development of the manufacture of a pop-up media book on topic 8 for first grade primary school students. It is anticipated that the construction of a pop-up media book would help the learning process by making it simpler for students in class I of MI Islamiyah Pancakarya Semarang to follow the thematic study in a more meaningful way.